2022
DOI: 10.3390/bs12070221
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Mobile Internet Use and Self-Rated and Mental Health of the Chinese Population: Evidence from China Family Panel Studies 2020

Abstract: With societal and technological developments, mobile Internet has become the most popular and widespread means to use the Internet in China. Thus, exploring the relationship between mobile Internet use and the self-rated health and mental health of the Chinese population is of great importance. This study empirically examined the impact of mobile Internet use on residents’ health using data from the China Family Panel Studies 2020 and conducted a heterogeneity analysis. The results revealed a significant negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The findings of this investigation corroborate the premise that persons of the middle age range and above may benefit greatly from using mobile Internet to strengthen their self-evaluated health and reduce their risk of developing chronic diseases. These findings are in line with what Li and Wang and colleagues found in their research [ 30 , 63 ]. Data shows that China’s 5G base stations account for > 60% of the global total, proving the success of China’s recent efforts to support the building of a digital China.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of this investigation corroborate the premise that persons of the middle age range and above may benefit greatly from using mobile Internet to strengthen their self-evaluated health and reduce their risk of developing chronic diseases. These findings are in line with what Li and Wang and colleagues found in their research [ 30 , 63 ]. Data shows that China’s 5G base stations account for > 60% of the global total, proving the success of China’s recent efforts to support the building of a digital China.…”
Section: Discussionsupporting
confidence: 93%
“…For example, while for girls, daily Internet use was not associated with higher levels of depressive symptoms [ 32 ], for boys, a positive association between the two factors did exist [ 33 ]. Interestingly, a study based on a Chinese sample found a significantly positive association between Internet use and mental health [ 34 ]. Many studies have also identified jealousy as one of the main symptoms of poorer states of mental health resulting from Internet use [ 35 , 36 , 37 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies have also identified jealousy as one of the main symptoms of poorer states of mental health resulting from Internet use [ 35 , 36 , 37 ]. In addition to psychological health, existing studies find a significant negative association between mobile Internet use and self-rated health [ 34 ]. Moreover, online games are one of the most significant applications of the Internet and their impacts are controversial.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Hou’s study found positive effects of Internet use on people’s self-rated physical health, objective physical health and mental health [ 46 ]. Li believes that Internet use can help with health improvement and self-assessment of chronic disease conditions [ 47 , 48 , 49 , 50 ]. Secondly, the use of the Internet is not conducive to health [ 51 ].…”
Section: Literature Reviewmentioning
confidence: 99%